Anti-hangup binary quantized DPLL technique for timing recovery in QAM symbol-rate sampled receivers. - Panayiotopoulos, I. (IEEE Transactions on communications)
This paper presents the statistical performance analysis of a decision directed timing recovery scheme based on a digital phase-locked loop (DPLL) that uses binary quantization and employs an adaptive sequential loop filter (LF) devised in order to prevent the adversary hang-up phenomenon. The proposed loop is analyzed by exercising Markovian analytical techniques on a simplified two-dimensional Markov chain approximation. Both the tracking and acquisition performances are examined in cases of M-ary quadrature amplitude modulation input signals. Numerical results, validated further by computer simulations, in essence show that the employed anti-hangup sequential LF speeds up the acquisition process by preventing the synchronizer from excessively long hang-ups. Compared to the classical nonadaptive binary quantized DPLL synchronizer, the loop with the proposed adaptation mechanism gains up to an order of magnitude in response time over the hang-up effect, at a minor cost in its steady-state tracking performance